Critical discourse analysis of proportional closed election system news (on the online media CNNindonesia.com and News.detik.com) - Prapti Wigati Purwaningrum; Danang Dwi Harmoko (Universitas Ahmad Dahlan, 2023)
The background of this research is the discourse on the implementation of a closed proportional system in the 2024 election. The research aims to find out the textual practices of the discourse of the two online media as information tools that can influence readers' opinions of a discourse. This study uses a qualitative descriptive method through a three-dimensional theoretical approach from Fairclough. Analysis of the object of research through three stages of analysis, description, interpretation and explanation. The results of the text analysis show that the two news media have different content. cnnindonesia.com seems to be answering the public's question mark about the reasons for PDIP as the only party that seems confident in supporting a closed proportional election system in the 2024 election. Through this system the chairman of the party absolutely appoints cadres in parliament. Meanwhile, news.detik.com's reporting places more emphasis on the possible impact that will be experienced by the PDIP and its implications for political developments in Indonesia if the system is implemented in the upcoming elections. From the two reports, there is a difference in the focus of representation and the purpose of the news. The conclusion is that the context of the media and the context of the communication situation appear to have a significant effect on determining the meaning of speech in online news media.